Sociodemographic construction in Córdoba (Argentina): changes of social structures in the territory and their impact on the demand for urban habitat - Boccolini, Sara María (Pontifícia Universidade Católica de São Paulo, 2017)
The si tuat ion in Córdoba (Argent ina) is revisited in terms of sociodemographic trends in the territory in a future short-term scenario. Demographic/territorial variables from official census data were combined, along with lifestyle and consumption variables surveyed by public and private consultants. This was complemented by a sociological analysis based on a review of the specific literature. Simultaneous macrocephaly and counterurbanization processes were detected, as well as changes in family structures and lifestyles, characteristic of the dialectic between the condition of an advanced demographic transition and processes of the current postmodern neoliberalism.